Preparation of Low-Dielectric-Constant Kaolin Clay Ceramics by Chemical Cleaning Method - Yang, Xiaobing; Yang, Weisen; Hu, Jiapeng (Frontiers in Materials, 2021)
Kaolin clay is an inexpensive and abundant material with potential for use as a low-dielectric-constant ceramic; however, the natural metallic oxides the clay contains hinder such applications. In this study, kaolin clay ceramics with excellent physical and dielectric properties were synthesized using kaolin clay as the raw material by chemical cleaning and sintering. Characterization of the resulting samples showed that the sulfuric acid treatment has a significant influence on the metallic oxide content and dielectric properties of the kaolin clay ceramics. When the kaolin clay raw material was treated with sulfuric acid three times, the dielectric constant decreased from 5.12 to 3.75 and the Vickers hardness increased from 946 to 1214 kg/mm2 relative to the ceramic prepared from the untreated clay. Therefore, these ceramics exhibit significant potential for use in the microelectronics industry.